2009 IEEE Electrical Design of Advanced Packaging &Amp; Systems Symposium (EDAPS) 2009
DOI: 10.1109/edaps.2009.5403978
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the gyro-resonance region modes by using the MoM for plasma column loaded cylindrical waveguide

Abstract: In this study, the dispersion curves of the plasma modes, which exist in gyroresonance region, have been obtained by using Method of Moment (MoM) for the plasma column loaded cylindrical waveguide. In the study, the first three modes, which have lowest degree, have been investigated. The validation of the method has been tested by comparing the exact solution of the structure which exists in the literature. Comparative results have been presented numerically and graphically. Besides absolute error curves have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The accuracy of the approximate solution enables computation of a narrower plane. In previous studies, the authors have shown the validation of the method in the gyro-resonance region for partially or fully plasma filled structures [56,57] and at plasma resonance region for fully [58] or partially [59] plasma filled structures. Additionally, they compared the method with two semi analytical methods, the quasi-static approximation and the asymptotic approximation, and they showed that the MoM is a better method than the other two methods for all frequencies of the gyro-resonance region [60].…”
Section: Methods Of Momentmentioning
confidence: 99%
“…The accuracy of the approximate solution enables computation of a narrower plane. In previous studies, the authors have shown the validation of the method in the gyro-resonance region for partially or fully plasma filled structures [56,57] and at plasma resonance region for fully [58] or partially [59] plasma filled structures. Additionally, they compared the method with two semi analytical methods, the quasi-static approximation and the asymptotic approximation, and they showed that the MoM is a better method than the other two methods for all frequencies of the gyro-resonance region [60].…”
Section: Methods Of Momentmentioning
confidence: 99%